Clinical characteristics and genetic analysis of children with Omicron BF.7.14 type novel coronavirus-related acute necrotizing encephalopathy - Zhang, Jianzhao; Sun, Jing; Li, Dongqing; Xie, Hua; Shangguan, Shaofang; Ge, Yangyang; Jiao, Hui; Ma, Caihui; Liu, Zhao; Zhao, Linqing; Yang, Jian (Frontiers in Neurology, 2024)
Background To explore the clinical characteristics, etiological factors, and clinical-related genetic variant of children with acute necrotizing encephalopathy (ANE) related to the Omicron BF.7.14 novel coronavirus. Methods Genomic variations were detected through whole exome sequencing. Additionally, we summarized the clinical data to explore the inheritance patterns associated with novel coronavirus-related ANE. Results This study included four patients (2 males and 2 females) with an average age of 2.78 ±1.93 years. All the patients had prodromal symptoms of Omicron BF.7.14 virus infection, and exhibited symptoms such as altered consciousness, seizures and cognitive/language disturbances. Cranial MRI scans revealed damage to the thalamus, basal ganglia and brainstem. The cerebrospinal fluid (CSF) cell counts were nearly normal, but protein level in CSF increased significantly. Genetic analysis revealed a novel truncated variant of CRMP2 gene in one patient who suffered more severe coma score and prognosis and dead in the later stages. All children exhibited a decrease in the absolute count of T lymphocytes, helper T cells, suppressor T cells, and NK cells to varying degrees. Furthermore, levels of cytokines, including IL-1 β, IL-5, IL-6 and IL-8 were significantly elevated in the CSF, especially in patient with truncated variant of CRMP2 gene. Conclusion The Omicron BF.7.14 type novel coronavirus can lead to ANE, characterized by T cell immunosuppression and a significant increase in cytokine levels in the CSF. The truncated variation of CRMP2 gene may affect the prognosis of ANE by affecting the migration of cerebral T cells.